Keberkesanan Latihan Modul Pemantapan Kecemerlangan Diri pada Jabatan Bahagian Sumber Manusia Setiausaha Kerajaan Negeri Kedah - Amin, Muhammad Isnan (2013)
Starting from the more difficult challenges of the world of work, workers need a training that could keep them up at work. Exercise Unit at Bahagian Sumber Manusia Setiausaha Kerajaan Negeri Kedah offers a form of training with the theme "latihan Modul Pemantapan Kecemerlangan Diri”. This training would provide method to build Boldness, Opportunity, adversity quotient, to create the spirit of excitement and enthusiasm (Zeal), to form a positive working attitude as well as to recognize and manage stress. Based on the purpose of training, researcher would like to examine the effectiveness of training. Therefore, researcher conducted a research with the title "Keberkesanan Latihan Modul Pemantapan Kecemerlangan Diri". This research has several objectives which are: what the factors that support and hinder the effectiveness of training, as well as the effectiveness of the training module brilliance of the Self Strengthening on doing work. In this study researcher using descriptive research methodology, in other words simply describe of any objective assessment found appropriately. From the results of the investigation, it is found that training module of self brilliance stabilization is considered "good". However,there are still some weaknesses that need to be improved in the future.